The Protocol for: Do peers enhance behavior change in group motivational interviewing? A translational clinical trial investigating brain synchrony in underage emerging adults during an fMRI hyperscanning task and association with alcohol use reductions - Sarah W. Feldstein Ewing; Genevieve F. Dash; Karen A. Hudson; Benedict Hyun; Manshu Yang; Linnea Stahl; Kristine Rømer Thomsen; Francesca M. Filbey (PLoS ONE, 2026)
US emerging adults under legal drinking age (underage emerging adults; U-EA; ages 18–19) are unlikely to seek or receive indicated health risk behavior interventions, thus it is imperative to find brief, effective interventions to reduce U-EA health risk behaviors, such as drinking. Developmental neuroscience reflects that peers hold higher neural salience during adolescence, as evidenced by differential neural response with real and/or simulated peers, even when those peers are not friends, and particularly in the context of alcohol. Peers also activate positive (prosocial) neural and health behavior responses among adolescents. The role of positive, prosocial peer feedback is consequential given that the most widely-used platforms for U-EA behavioral interventions are group-based platforms. We propose functional magnetic resonance imaging (fMRI) hyperscanning (tandem dyadic scanning) to evaluate U-EA brain response during group motivational interviewing (GMI) for health behavior change. This study will enroll n = 248 U-EA (ages 18–19) with ≥1 past month binge drinking event (4/3 standard drinks per occasion for males/females) via community and university campus recruitment and deliver group MI to peer dyads (no comparator; within-subjects design; ClinicalTrials.gov ID: NCT06115252). Synchronized fMRI (hyperscanning) will be used to examine brain response to positive, prosocial peer-directed health promotive language (peer-directed change talk) generated during and extracted from the GMI session. Primary outcomes include fMRI-based hyperscanning metrics (BOLD synchrony in social cognition network) and their association with behavioral measures (past-month alcohol use days measured via Timeline Followback) at 12-months (primary outcome) and 3- and 6-months (secondary outcomes) post-GMI. We hypothesize that greater neural alignment in the social cognition network during positive, prosocial peer interactions (peer-directed change talk) will be associated with greater post-intervention behavior change (lower number of past month drinking days) at each follow-up point. This translational study is crucial for making meaningful gains in improving interventions for youth health behavior. Trial registration ClinicalTrials.gov NCT06115252